Coke-softening, oil-controlling and makeup-maintaining composite powder for cosmetics and preparation method thereof

By combining the multi-porous high specific surface area silica with soft-focus light-weight modified powder, a soft-focus oil-controlled makeup-holding composite powder for cosmetics was prepared, which solved the makeup-holding effect and natural feeling of existing cosmetic powders in hot weather. The poor problem achieves the effect of efficient oil absorption and natural skin modification.

CN119454485APending Publication Date: 2025-02-18CHUZHOU KEYI DAILY CHEMICAL PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411359006.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

It is difficult for existing cosmetic powders to maintain makeup effect and natural feeling in hot weather, and commonly used functional composite powders have problems with limited ingredient usage and poor skin feeling.

Method used

A composite of silicone with soft-coke and lightweight modified powder for cosmetics was prepared by modifying two-dimensional sheet-like structure powder and porous structure. The combination of silica has significant sebum oil absorption function and good makeup fixation effect.

Benefits of technology

This composite powder can efficiently absorb excess secreted sebum, keeping the makeup feeling clean and natural, with a light texture, and a unique matte fog feel can better modify the skin, solving the problem of makeup holding and natural feeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005064444650000011
    Figure HDA0005064444650000011
  • Figure HDA0005064444650000012
    Figure HDA0005064444650000012
  • Figure HDA0005064444650000021
    Figure HDA0005064444650000021
Patent Text Reader

Abstract

The invention provides soft-coke oil-control makeup-holding composite powder for cosmetics and a preparation method of the soft-coke oil-control makeup-holding composite powder, belongs to the technical field of cosmetic powder, and solves the technical problems of short makeup-holding time, unnatural makeup feeling and the like in the prior art. The composite powder provided by the invention comprises the following components: a component I: 45-85 parts by mass of modified two-dimensional sheet structure powder; 25-55 parts by mass of silica with a porous structure, the porous structure of the silica can increase the specific surface area and enhance the oil absorption capacity, the skin feeling is lighter, and a certain soft coke effect is achieved; and a component III: 0-10 parts by mass of a surface treating agent. According to the prepared composite powder, the oil control capacity is improved, meanwhile, the product can be endowed with light skin feeling and an excellent soft coke effect, the purposes of keeping makeup and controlling oil can be achieved, and meanwhile the phenomena that after a consumer makes up, oil is absorbed darkly, and the brightness is too high and unnatural are effectively prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cosmetic powders, and relates to a cosmetic powder and a preparation method thereof, in particular to a cosmetic soft-focus, oil-controlling, long-lasting makeup composite powder and a preparation method thereof. Background Art

[0002] In addition to sun protection, the most troublesome problem in summer is makeup smudges. In hot weather, people sweat a lot, and carefully applied makeup will be ruined once they sweat while commuting outdoors, which seriously affects the consumer experience. Currently, in cosmetics products, especially color cosmetics, how to achieve makeup lasting and oil control, maintain a matte and natural feel, and prevent dullness after makeup has become a major concern in the industry.

[0003] At present, the main ways to prevent dullness after makeup are to use powder raw materials with low oil absorption and color difference and some functional composite powders with selective oil absorption. However, both methods have certain problems. Generally, powders with low oil absorption and color difference can brighten the skin tone, but their excessive glossiness can easily lead to problems such as unnatural makeup. In addition, the selectively adsorbed functional powders, due to the addition of a large amount of zinc oxide and hydroxyapatite and other ingredients, lead to problems such as the raw materials being astringent and fake white, and the makeup being unnatural. There are also problems with the limited use of ingredients, so they cannot be added in large quantities in the formula.

[0004] In order to solve the above problems and achieve the effect of long-lasting makeup and soft-focus natural effect after applying makeup, the present invention adopts a new porous high specific surface area silica and a soft-focus light modified powder for compounding, and proposes a soft-focus oil-control long-lasting makeup composite powder for cosmetics and a preparation method thereof. The powder has a significant sebum oil absorption function, can efficiently absorb excess sebum secretion without safety risks, has a good makeup-setting effect, and the makeup feels cleaner and more natural, with a light texture and a unique matte mist feeling that can better modify the skin. Summary of the invention

[0005] The first purpose of the present invention is to address the above-mentioned problems in the existing technology and to propose a soft-focus, oil-control and long-lasting makeup composite powder for cosmetics. The technical problem to be solved by the invention is: how to achieve long-lasting makeup and a soft-focus and natural effect after applying makeup.

[0006] The first object of the present invention can be achieved by the following technical solutions:

[0007] A soft-focus, oil-controlling, long-lasting makeup composite powder for cosmetics, characterized by comprising the following components:

[0008] Component 1: modified two-dimensional flake structure powder, 45-85 parts by weight;

[0009] Component 2: porous silica, 25-55 parts by weight;

[0010] Component three: surface treatment agent, 2-5 parts by mass.

[0011] Furthermore, the modified two-dimensional flaky structure powder in component one uses one or more combinations of synthetic fluorphlogopite, mica, talc, and boron nitride as a base material, and the modifier is vinyl dimethyl silane.

[0012] Furthermore, the specific surface area of ​​the porous silica in component 2 is 640-730 m 2 / g, particle size is 4-7μm; there are many tiny gaps on the surface and inside of the porous silica, which is rough and not smooth, and has a soft focus effect.

[0013] Furthermore, the surface treatment agent in component three is one or more of triethoxyoctylsilane, polydimethylsiloxane, polymethylsiloxane and aminopolydimethylsiloxane.

[0014] The second purpose of the present invention is to address the above-mentioned problems in the existing technology and to propose a method for preparing a soft-focus, oil-controlling, long-lasting composite powder for cosmetics. The technical problem to be solved by the invention is: how to prepare a long-lasting, oil-controlling cosmetic powder.

[0015] The second object of the present invention can be achieved by the following technical solutions:

[0016] A method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics, characterized by comprising the following steps:

[0017] S1: Prepare modified two-dimensional flake structure powder, and filter to obtain paste 1;

[0018] S2: preparing silica with a porous structure and filtering to obtain paste 2;

[0019] S3: Paste 1 in S1 and paste 2 in S2 are mixed and homogenized in a kneader, and then ammonia water and a surface treatment agent are added thereto for mixing and reaction to obtain hydrophobic paste 3;

[0020] S4: Drying the hydrophobic paste 3 in S3, crushing and classifying after drying to obtain a finished product.

[0021] Furthermore, S1 includes the following steps:

[0022] S1.1: Add 5-8 times the mass of deionized water into the 5-15μm two-dimensional sheet structure powder, and then add analytical pure anhydrous ethanol and aluminum sulfate to mix. The mass ratio of analytical pure anhydrous ethanol, aluminum sulfate and deionized water is 5:0.2:100. The mixture slurry is dispersed at high speed for 30 minutes, and then transferred to a homogenizer for high-speed homogenization to obtain a uniformly dispersed slurry;

[0023] S1.2: Put the pre-made slurry into a reactor, add vinyldimethylsilane thereto and stir at a stirring speed of 100 rpm, a reaction temperature of 65°C, and a reaction time of 1-2.5 hours;

[0024] S1.3: Take out the slurry after the reaction is completed, put it into a suction filter for suction filtration, and the suction filtration pressure is 0.05-0.1mbar to obtain paste 1 in component 1.

[0025] Further, S2 includes the following steps:

[0026] S2.1: Add high-purity solid spherical silicon powder with an average particle size of 5 μm into a polytetrafluoroethylene microwave reactor, add deionized water 3-5 times its mass, and add hydrofluoric acid and hydrogen peroxide, the mass ratio of hydrofluoric acid, hydrogen peroxide and deionized water is 2:3.5:100, start stirring and microwave heating, the stirring speed is 200 rpm, the heating program is set to 80°C heating for 15 min, 100°C heating for 20 min, 120°C heating for 30 min, 150°C heating for 10 min, cool, and wash with deionized water until the pH is 5-7;

[0027] S2.2: Put the slurry in Step 2.1 into a polytetrafluoroethylene negative pressure reactor, add deionized water at 3-5 times the solid content, and add potassium carbonate thereto, the mass ratio of potassium carbonate to deionized water is 8.5:100, after it is fully dissolved, start vacuuming and high-speed stirring, the negative pressure is 0.05-0.08mbar, the stirring speed is 200-300rpm, the reaction time is 1.5-3h, the reaction is completed, and washing is performed until the pH is 6-8;

[0028] S2.3: The washed slurry is put into a suction filter for suction filtration at a suction pressure of 0.1 mbar to obtain paste 2 in component 2.

[0029] Further, S3 specifically places paste one and paste two in a kneader, starts stirring, adds ammonia water and a surface treatment agent while stirring, sets the kneading speed to 30-50rpm, and the mass ratio of ammonia water, surface treatment agent and solid content is 1.5-3.5:2-5:100, and kneading is continued for 20-40 minutes.

[0030] Further, S4 includes the following steps:

[0031] S4.1: The hydrophobic paste obtained in S3 is placed in a freeze drying oven for drying, the freezing temperature is set at -40°C, and the drying is performed for 14-18 hours, and then the temperature is raised to 40-60°C, and the drying is continued for 6-8 hours;

[0032] S4.2: Take out the dried material and put it into a pulverizer for pulverization. The pulverized material is sieved and impurities are removed using a 100-180 mesh vibrating screen to obtain a finished product.

[0033] Compared with the prior art, the soft-focus oil-controlling long-lasting makeup composite powder for cosmetics and its preparation method have the following advantages:

[0034] 1. The composite powder of the present invention is compounded with a new porous high specific surface area silica and a soft-focus light modified powder. The powder has a significant sebum oil absorption function, efficiently absorbs excess sebum secretion without safety risks, has a good makeup-setting effect, and makes the makeup look cleaner and more natural. The texture is light, and the unique matte mist feeling can better modify the skin.

[0035] 2. In the preparation method of the present invention, a two-dimensional sheet structure material is used as a substrate, wet dispersed, and vinyl dimethyl silane is used to graft and coat the surface of the substrate and in-situ polymerize to form a dense vinyl polydimethylsiloxane network coating layer on the surface of the substrate. Compared with a powder substrate that is not coated or directly coated with vinyl polydimethylsiloxane, the product of the present invention has a higher coating rate, a small oil absorption color difference, a light touch, and a better matte soft focus effect.

[0036] 3. The preparation method of the present invention starts with solid spherical silicon powder commonly found on the market, and adopts microwave digestion etching and negative pressure cracking multi-channel processes to prepare porous spherical silicon powder with high specific surface area. Compared with commercially available solid spherical silicon and porous spherical silicon, the spherical silicon powder in the present invention has higher porosity and specific surface area, higher oil absorption capacity, lighter specific gravity and touch, and the surface is digested and etched to form a matte plush shape with matte soft focus and velvety feel.

[0037] 4. Conventional high-temperature drying, on the one hand, has low and insufficient water removal efficiency for high-water content materials, especially porous silica products, and on the other hand, long-term high temperature will cause certain damage to the surface coating of the substrate, which will have an adverse effect on the skin feel of the product. Therefore, in the preparation method of the present invention, the two-dimensional sheet structure powder and the spherical powder are combined to form a spherical sheet effect, which is beneficial to the dispersion, surface treatment and skin feel of the powder. At the same time, freeze drying can better maintain the effect of surface modification and fully remove the water inside the porous silica. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a comparison chart of the hydrophobicity of the modified two-dimensional flaky structure powder of the present invention and the powder modified by conventional process.

[0039] Figure 2 It is a comparison chart of the oil absorption color difference between the modified two-dimensional flaky structure powder of the present invention and the powder modified by the conventional process.

[0040] Figure 3 It is a scanning electron microscope image of the porous structure silica of the present invention.

[0041] Figure 4 This is a scanning electron microscope image of conventional commercially available porous silica.

[0042] Figure 5 It is a comparison chart of the oil absorption color difference between the porous structure silica of the present invention and conventional commercially available porous silica.

[0043] Figure 6 This is a scanning electron microscope image of Example 1.

[0044] Figure 7 It is a comparison chart of the oil absorption color difference between Example 1 and Comparative Example 1 and Comparative Example 2.

[0045] Figure 8 It is a comparison diagram of the hydrophobicity of Example 1, Comparative Example 1 and Comparative Example 2.

[0046] Fig. 9 The present invention is a comparative table of the soft focus index and skin feel test of the modified two-dimensional flake structure powder and the powder modified by the conventional process.

[0047] Fig.10 The table is a comparison table of various indexes of the porous silica of the present invention and conventional commercially available porous silica.

[0048] Fig.11 It is a comparison table of various index tests of the embodiments and comparative examples.

[0049] Fig.12 It is a test table of makeup lasting effect of embodiments and comparative examples. DETAILED DESCRIPTION

[0050] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0051] The present invention proposes a preparation process of a modified two-dimensional flaky structure powder. The modified powder manufactured by the present invention has a higher coverage rate, small oil absorption color difference, light touch, better matte soft focus effect, and can improve the makeup holding and soft focus performance to a certain extent; at the same time, the present invention also proposes a special porous high specific surface area spherical silica manufacturing process. The surface properties and internal void structure of the spherical silica manufactured by the present invention have been significantly changed, so that it has a higher porosity and specific surface area, a higher oil absorption capacity and a lighter specific gravity and touch. The surface is digested and etched to form a matte plush shape with matte soft focus and velvet feeling. After the two are compounded and further surface treated, the makeup can have strong oil control and makeup holding and a natural matte soft focus feeling.

[0052] The composite powder includes the following components:

[0053] Component 1: modified two-dimensional flake structure powder, 45-85 parts by weight;

[0054] Component 2: porous silica, 25-55 parts by weight;

[0055] Component three: surface treatment agent, 2-5 parts by mass.

[0056] The modified two-dimensional sheet structure powder in component one uses one or more combinations of synthetic fluorphlogopite, mica, talc, and boron nitride as a base material, and the modifier is vinyl dimethyl silane. The modified powder manufactured by the present invention has a higher coverage rate, small oil absorption color difference, light touch, better matte soft focus effect, and can improve the makeup holding and soft focus performance to a certain extent.

[0057] As for the modified two-dimensional flake structure powder of the present invention having the characteristics of higher coverage, smaller oil absorption color difference and better touch, in fact, the present invention proposes a special processing process for the two-dimensional flake structure powder, which specifically includes the following steps:

[0058] Add 5-8 times the mass of deionized water into the 5-15 μm two-dimensional sheet structure powder, then add analytical pure anhydrous ethanol and aluminum sulfate to mix, the mass ratio of analytical pure anhydrous ethanol, aluminum sulfate and deionized water is 5:0.2:100, disperse the mixture slurry at high speed for 30 minutes, and then transfer it to a homogenizer for high-speed homogenization to obtain a uniformly dispersed slurry;

[0059] The prefabricated slurry was placed in a reaction kettle, and vinyldimethylsilane was added thereto for stirring at a stirring speed of 100 rpm, a reaction temperature of 65°C, and a reaction time of 1-2.5 hours;

[0060] The slurry after the reaction is taken out, and put into a suction filter for suction filtration, and the suction filtration pressure is 0.05-0.1mbar, to obtain paste one in component one, and the paste one is conventionally dried to obtain powder of component one.

[0061] The modified two-dimensional sheet structure powder in component one is different from the conventional dry modified powder. The conventional dry modified process generally puts the commercially available vinyl polydimethylsiloxane and the powder into a high-speed mixer for mixing, and then bakes and crushes to obtain the finished product. The specific difference is that the modified two-dimensional sheet structure powder of the present invention has a better coating effect, a higher activation index, and the treatment agent is more densely bound to the surface of the substrate, which is intuitively manifested in the difference in dynamic hydrophobicity, small oil absorption color difference, higher soft focus index and better skin feel.

[0062] from Figure 1It can be seen that the modified two-dimensional lamellar structure powder of the present invention is almost insoluble in water after severe shaking, while the conventional modified powder is mostly soluble in water, indicating that the modified two-dimensional lamellar structure powder of the present invention has better hydrophobicity.

[0063] from Figure 2 It can be seen that the modified two-dimensional lamellar structure powder of the present invention only slightly changes color after absorbing simulated artificial sebum, while the conventional modified powder changes color more seriously, indicating that the modified two-dimensional lamellar structure powder of the present invention has smaller oil absorption color difference.

[0064] Furthermore, the two modified powders were tested for soft focus index and skin feel. The soft focus index test was to mix the sample to be tested with the resin in a certain proportion, apply it on the spider web chart using a film applicator, and place it in a colorimetric box to observe the soft focus effect. The index was 1-5 levels. The larger the number, the better the soft focus effect. The skin feel test was to randomly select 3 technicians to perform skin smear tests separately. The above test results are shown in Fig. 9 .

[0065] Secondly, the porous silica in component 2 is different from conventional commercially available porous silica. The porous silica in the present invention has a higher porosity and specific surface area. The surface is etched to form a matte plush surface. The specific surface area of ​​the porous silica in component 2 is 640-730 m 2 / g.

[0066] As for the porous silica of the present invention having higher porosity and specific surface area and a matte plush appearance, the present invention actually proposes a special manufacturing process for the porous silica, which specifically includes the following steps:

[0067] Put high-purity solid spherical silicon powder with an average particle size of 5 μm into a polytetrafluoroethylene microwave reactor, then put deionized water 3-5 times its mass into it, and put hydrofluoric acid and hydrogen peroxide into it, the mass ratio of hydrofluoric acid, hydrogen peroxide and deionized water is 2:3.5:100, start stirring and microwave heating, the stirring speed is 200 rpm, the heating program is set to 80°C heating for 15 minutes, 100°C heating for 20 minutes, 120°C heating for 30 minutes, and 150°C heating for 10 minutes, cool, and wash with deionized water until the pH is 5-7;

[0068] Put the slurry in Step 2.1 into a polytetrafluoroethylene negative pressure reactor, add deionized water at 3-5 times the solid content, and add potassium carbonate, the mass ratio of potassium carbonate to deionized water is 8.5:100. After it is fully dissolved, start vacuuming and high-speed stirring, the negative pressure is 0.05-0.08mbar, the stirring speed is 200-300rpm, the reaction time is 1.5-3h, the reaction is completed, and washing is performed until the pH is 6-8;

[0069] The washed slurry was put into a suction filter for suction filtration at a suction pressure of 0.1 mbar to obtain paste 2 of component 2. The paste 2 was conventionally dried to obtain porous silica of component 2.

[0070] The porous silica in component two is different from conventional commercially available porous silica. The specific difference is that the porous silica in the present invention has more and denser pores, and the surface has a certain plush feeling. The performance is intuitively manifested in a larger specific surface area, a higher simulated sebum oil absorption value, a small oil absorption color difference, a higher soft focus index and a better skin feel.

[0071] from Figure 3 and Figure 4 It can be seen from the electron microscope image that the porous silica surface of the present invention has significantly more and denser pores and has a certain velvety feel, while the conventional commercially available porous silica surface has relatively fewer pores and a poor velvety feel.

[0072] from Figure 5 It can be seen that the porous silica of the present invention changes color only slightly after absorbing simulated artificial sebum, while the conventional commercially available porous silica changes color more seriously, indicating that the porous silica of the present invention has a smaller oil absorption color difference.

[0073] Furthermore, the specific surface area, soft focus index and skin feel of the two modified powders were tested. The above test results are shown in Fig.10 .

[0074] The surface treatment agent in component three is one or more of triethoxyoctylsilane, polydimethylsiloxane, polymethylsiloxane and aminopolydimethylsiloxane.

[0075] In order to verify the beneficial effects of the present invention, based on the new modified two-dimensional flaky structure powder and porous silica proposed in the above content, the present invention also proposes a method for preparing a soft-focus oil-controlling long-lasting makeup composite powder for cosmetics, comprising the following steps:

[0076] Prepare a modified two-dimensional flaky structure powder, specifically the above-mentioned modified powder, to obtain a paste 1;

[0077] Prepare silica with a porous structure, specifically the specially prepared silica mentioned above, to obtain paste 2;

[0078] Place paste one and paste two in a kneader, start stirring, add ammonia water and surface treatment agent while stirring, set the kneading speed to 30-50rpm, the mass ratio of ammonia water, surface treatment agent and solid content is 1.5-3.5:2-5:100, and continue kneading for 20-40 minutes to obtain hydrophobic paste three.

[0079] The hydrophobic paste is sent to a freeze drying box for drying, the freezing temperature is set to -40°C, dried for 14-18 hours, then heated to 40-60°C, and continued to dry for 6-8 hours; the dried material is taken out and put into a pulverizer for crushing, and the crushed material is sieved and removed with a 100-180 mesh vibrating screen to obtain a finished product.

[0080] According to the above-mentioned method for preparing powder, the present invention provides the following examples and comparative examples for comparison with the examples.

[0081] Example 1

[0082] A soft-focus, oil-control and long-lasting makeup composite powder for cosmetics is prepared according to the above process and has the following components: component one: synthetic fluorphlogopite with an average particle size of 10 μm that has been surface-modified by the process of the present invention, with a mass fraction of 55 parts; component two: silica with a porous structure prepared by the above process of the present invention, with an average particle size of 5 μm, with a mass fraction of 42 parts; component three: triethoxyoctylsilane, with a mass fraction of 3 parts.

[0083] Comparative Example 1

[0084] The invention has the following components: component 1: synthetic fluorphlogopite with an average particle size of 10 μm, which has been surface-modified by ordinary dry mixing, with a mass fraction of 55 parts; component 2: ordinary commercially available porous silica with an average particle size of 5 μm, with a mass fraction of 42 parts; component 3: triethoxyoctylsilane, with a mass fraction of 3 parts. The drying process is the same as that of Example 1, and freeze drying is adopted.

[0085] Comparative Example 2

[0086] The composition includes the following components: component 1: synthetic fluorphlogopite with an average particle size of 10 μm after surface modification by the process of the present invention, with a mass fraction of 55 parts; component 2: silica with a porous structure prepared by the process of the present invention, with an average particle size of 5 μm, with a mass fraction of 42 parts; component 3: triethoxyoctylsilane, with a mass fraction of 3 parts. The drying process in Step 4 is ordinary constant temperature forced air drying, and the temperature is set to 100°C.

[0087] For the above-mentioned Example 1 and Comparative Examples 1, 2, and 3, oil absorption and discoloration tests, simulated sebum oil absorption tests, hydrophobicity, soft focus index tests, skin feel tests, 105°C volatile matter tests, and makeup holding tests were performed respectively. The difference between Example 1 and Comparative Example 1 is that Comparative Example 1 uses synthetic fluorphlogopite and common commercially available porous silica prepared by conventional surface modification processes, and Comparative Example 2 uses a common constant temperature forced air drying process to dry the product, thereby confirming the difference between the process of the present invention and the conventional preparation process commonly used at present.

[0088] Figure 6This is a scanning electron microscope image of Example 1. It can be seen that the two-dimensional sheet structure powder and the spherical powder are combined to form a spherical sheet effect, which is beneficial to the dispersion of the powder.

[0089] from Figure 7 It can be seen that Example 1 has only a slight discoloration after absorbing the simulated artificial sebum, while the discoloration of Comparative Example 2 is relatively slightly obvious, and the discoloration of Comparative Example 1 is the most serious, indicating that the modified two-dimensional flaky structure powder and porous structure silica prepared by the present invention can effectively reduce the problem of oil absorption and discoloration after compounding and surface treatment. At the same time, the freeze-drying process is better than conventional high-temperature drying for maintaining the powder structure and surface treatment effect.

[0090] Figure 8 The hydrophobicity comparison between the examples and the comparative examples shows that Example 1 is almost insoluble in water after severe shaking, while both Comparative Examples 1 and 2 are soluble in water to varying degrees, indicating that the modified two-dimensional lamellar structure powder and freeze-drying process of the present invention can improve the coating effect of the finished product.

[0091] Further, the examples and comparative examples were subjected to simulated sebum oil absorption test, 120°C volatile matter test, soft focus index and skin feel test. The above test results are shown in Fig.11 .

[0092] Furthermore, the makeup lasting performance test was performed on the embodiments and comparative examples, and the makeup lasting effect test method is as follows.

[0093] The laboratory randomly selected 20 healthy women aged between 25 and 30 years old and randomly divided them into 4 groups, with 5 people in each group. The test results were taken as the average value of each group. Among them, 3 groups of testers performed facial cleansing under uniform conditions in the same environment. Professional makeup artists made makeup preparations such as applying lotion according to uniform standards, and then applied the powders of Example 1 and Comparative Examples 1-2 to the faces of the corresponding testers in equal amounts. The other group of testers was a blank group, which performed facial cleansing and makeup preparations according to the same standards as the above 3 groups of testers, but did not use any powder for makeup. Finally, the Cutometer MPA 580 skin tester was used to measure the skin oil secretion (μg / cm 2 ) to test, the results are shown in Fig.12 .

[0094] In summary, the soft-focus, oil-control and long-lasting makeup composite powder for cosmetics of the present invention can not only efficiently absorb sebum to achieve the purpose of long-lasting makeup and oil control, but also enhance the matte and soft-focus effect of the makeup surface to make the makeup effect more natural.

[0095] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A soft-focus, oil-controlling, long-lasting makeup composite powder for cosmetics, characterized in that: The components include: Component 1: modified two-dimensional flake structure powder, 45-85 parts by weight; Component 2: porous silica, 25-55 parts by weight; Component three: surface treatment agent, 2-5 parts by mass.

2. A soft-focus, oil-controlling, long-lasting makeup composite powder for cosmetics according to claim 1, characterized in that: The modified two-dimensional flaky structure powder in component one adopts one or more combinations of synthetic fluorphlogopite, mica, talc and boron nitride as a base material, and the modifier is vinyl dimethyl silane.

3. The soft-focus, oil-controlling, long-lasting makeup composite powder for cosmetics according to claim 1, characterized in that: The specific surface area of ​​porous silica in component 2 is 640-730m 2 / g, particle size is 4-7μm; the surface and interior of the porous silica have many tiny gaps, it is rough and not smooth, and has a soft focus effect.

4. The soft-focus, oil-controlling, long-lasting makeup composite powder for cosmetics according to claim 1, characterized in that: The surface treatment agent in component three is one or more of triethoxyoctylsilane, polydimethylsiloxane, polymethylsiloxane and aminopolydimethylsiloxane.

5. A method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics, characterized in that: The steps include: S1: Prepare modified two-dimensional flake structure powder, and filter to obtain paste 1; S2: preparing silica with a porous structure and filtering to obtain paste 2; S3: Paste 1 in S1 and paste 2 in S2 are mixed and homogenized in a kneader, and then ammonia water and a surface treatment agent are added thereto for mixing and reaction to obtain hydrophobic paste 3; S4: Drying the hydrophobic paste 3 in S3, crushing and classifying after drying to obtain a finished product.

6. The method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics according to claim 5, characterized in that: S1 includes the following steps: S1.1: Add 5-8 times the mass of deionized water into the 5-15μm two-dimensional sheet structure powder, and then add analytical pure anhydrous ethanol and aluminum sulfate to mix. The mass ratio of analytical pure anhydrous ethanol, aluminum sulfate and deionized water is 5:0.2:

100. The mixture slurry is dispersed at high speed for 30 minutes, and then transferred to a homogenizer for high-speed homogenization to obtain a uniformly dispersed slurry; S1.2: Put the pre-made slurry into a reactor, add vinyldimethylsilane thereto and stir at a stirring speed of 100 rpm, a reaction temperature of 65°C, and a reaction time of 1-2.5 hours; S1.3: Take out the slurry after the reaction is completed, put it into a suction filter for suction filtration, and the suction filtration pressure is 0.05-0.1mbar to obtain paste 1 in component 1.

7. The method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics according to claim 5, characterized in that: S2 includes the following steps: S2.1: Add high-purity solid spherical silicon powder with an average particle size of 5 μm into a polytetrafluoroethylene microwave reactor, add deionized water 3-5 times its mass, and add hydrofluoric acid and hydrogen peroxide, the mass ratio of hydrofluoric acid, hydrogen peroxide and deionized water is 2:3.5:100, start stirring and microwave heating, the stirring speed is 200 rpm, the heating program is set to 80°C heating for 15 min, 100°C heating for 20 min, 120°C heating for 30 min, 150°C heating for 10 min, cool, and wash with deionized water until the pH is 5-7; S2.2: Put the slurry in Step 2.1 into a polytetrafluoroethylene negative pressure reactor, add deionized water at 3-5 times the solid content, and add potassium carbonate thereto, the mass ratio of potassium carbonate to deionized water is 8.5:100, after it is fully dissolved, start vacuuming and high-speed stirring, the negative pressure is 0.05-0.08mbar, the stirring speed is 200-300rpm, the reaction time is 1.5-3h, the reaction is completed, and washing is performed until the pH is 6-8; S2.3: The washed slurry is put into a suction filter for suction filtration at a suction pressure of 0.1 mbar to obtain paste 2 in component 2.

8. The method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics according to claim 5, characterized in that: S3 specifically includes placing paste 1 and paste 2 in a kneader, starting stirring, adding ammonia water and a surface treatment agent while stirring, setting the kneading speed to 30-50rpm, the mass ratio of ammonia water, surface treatment agent to solid content to 1.5-3.5:2-5:100, and kneading continuously for 20-40 minutes.

9. The method for preparing the soft-focus, oil-controlling and long-lasting makeup composite powder for cosmetics according to claim 5, characterized in that: S4 includes the following steps: S4.1: The hydrophobic paste obtained in S3 is placed in a freeze drying oven for drying, the freezing temperature is set at -40°C, and the drying is performed for 14-18 hours, and then the temperature is raised to 40-60°C, and the drying is continued for 6-8 hours; S4.2: Take out the dried material and put it into a pulverizer for pulverization. The pulverized material is sieved and impurities are removed using a 100-180 mesh vibrating screen to obtain a finished product.